Molecular Identification of Endophytic Bacteria Isolated From Allium cepa L. Waste as Antibiofilm Agent Against S.mutans - Ekajayanti Kining; Dian Firdiani; Sogandi; Muh. Achyar Ardat (UIN Sunan Gunung Djati Bandung, 2025)
Streptococcus mutans is a key contributor to dental caries due to its ability to form resilient biofilms. Endophytic bacteria are a promising source of natural antibiofilm agents. This study aimed to isolate and characterize endophytic bacteria from red onion (Allium cepa L) waste with potential antibiofilm activity against S. mutans. This research employed an exploratory laboratory design with descriptive and quantitative approaches. Morphological and Gram-staining analyses were conducted alongside molecular identification through 16S rRNA sequencing. Antibacterial and antibiofilm assays were performed to evaluate the biological activity of isolate EA1. Absorbance values from biofilm inhibition and degradation tests were analyzed using descriptive statistics to calculate inhibition percentages. Isolate EA1 exhibited strong biofilm degradation (77% inhibition), moderate inhibition of biofilm formation (53%), and relatively lower antibacterial activity (30% growth inhibition). Molecular analysis confirmed its identity as a member of the Enterobacter genus, closely related to E. tabaci and E. asburiae. EA1 holds significant potential as a source of novel antibiofilm compounds for controlling S. mutans. Further investigation is needed to characterize its active metabolites and evaluate its clinical applicability.